Non-intermittent cooperative downloading approach for VANET - Yong XIE; bing WULi; xiang HEYan; Jing FAN; yi LIUBing (Tongxin xuebao)
Internet access through access points (AP) for vehicles has the advantages of low cost, high-bandwidth and low latency. However,because of dark area (DA) around AP, vehicles have to take interm tent linking to Internet, result-ing in the QoS of network is difficult to be guaranteed.A non-intermittent cooperative downloading method (NICDM)for highway was proposed. The unfinished download task of target vehicular in current AP was decomposed into several parts according to vehicle's speed, the size of unfinished task and distance of DA, then commissioned to two nearest APs. A group of cooperative vehicles selected under selection strategy would get data from the APs and forward it to the target vehicle when theymeet in DA.And an N -replicaconflict resolution strategy was used to improve the stability of coopera-tive downloading. Simulation results show that compared with similar cooperative methods, NICDM can uninterruptedly get cooperative download data through DAs and improve system's QoS and throughput.